2020
DOI: 10.1148/radiol.2020191272
|View full text |Cite
|
Sign up to set email alerts
|

Three-year Survival Rate after Radiofrequency Ablation for Surgically Resectable Colorectal Lung Metastases: A Prospective Multicenter Study

Abstract: VASCULAR AND INTERVENTIONAL RADIOLOGYC olorectal cancer (CRC) is one of the most common malignancies in the world, with metastases to the lungs in approximately 10%-20% of patients (1). Surgery is performed when both the primary tumor and the lung metastases are completely resectable, with a 3-year overall survival (OS) rate of 53%-82% after lung metastasectomy (2-6). Systemic chemotherapy is administered for patients who are not candidates for surgery, but its 3-year OS rate is less than 50% (7,8). Stereotact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
45
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 38 publications
0
45
3
Order By: Relevance
“…In the most important (prospective and multicenter) and recently published study on this subject, Hasegawa et al reported a series of 70 patients with lung metastases from colorectal cancer of < 3 cm treated with RFA an OS rate at 3 years of 84%, with hardly any complications (1% of severe complications). Factors associated with a worse OS include a rectal rather than a colon origin and the absence of chemotherapy [93]. Unlike NSCLC, several published studies have evaluated the value of MWA in OLD.…”
Section: Oligometastatic Lung Diseasementioning
confidence: 99%
“…In the most important (prospective and multicenter) and recently published study on this subject, Hasegawa et al reported a series of 70 patients with lung metastases from colorectal cancer of < 3 cm treated with RFA an OS rate at 3 years of 84%, with hardly any complications (1% of severe complications). Factors associated with a worse OS include a rectal rather than a colon origin and the absence of chemotherapy [93]. Unlike NSCLC, several published studies have evaluated the value of MWA in OLD.…”
Section: Oligometastatic Lung Diseasementioning
confidence: 99%
“…The first pulmonary RFA procedure was described in 2000 [5], and multiple studies have shown low rates of complications [6][7][8]. Local tumor control is comparable to wedge resection or stereotactic body radiation therapy for metastasis [9,10]. Recent guidelines for colorectal cancer metastases clearly indicate that ablation is recommended as a free-standing therapy or in combination with resection, whereas stereotactic body radiation therapy is indicated only for selected patients not amenable to resection or within a clinical trial [11].…”
Section: Introductionmentioning
confidence: 99%
“…The application of radiofrequency ablation (RFA) for the treatment of malignant lung tumors is increasing [1][2][3][4][5]. Several studies have detected risk factors for local tumor progression after lung RFA, including tumor size, histology, and contact with major vessels [2][3][4], with large tumor size as the factor mentioned most frequently.…”
Section: Introductionmentioning
confidence: 99%